1985
DOI: 10.1111/j.1399-6576.1985.tb02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane v Fentanyl for Outpatient Laparoscopy

Abstract: Isoflurane and fentanyl have been compared as anaesthetic agents for outpatient laparoscopy. In 50 female patients anaesthesia was induced with thiopentone and maintained with nitrous oxide 66% in oxygen combined with either isoflurane 1-2% or fentanyl 0.3 mg according to a randomized list. Suxamethonium was used to facilitate intubation and for further muscle relaxation. Immediate recovery from anaesthesia was assessed by eye opening and time before giving the date of birth. Additional observations made hourl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Postoperative nausea and vomiting continue to be common in spite of advances in the techniques used in general anaesthesia. This is especially true in female patients (19,20). The frequency of postoperative emetic sequelae varies widely between different studies; figures as high as 83% have been reported (21).…”
Section: Many Pharmacological and Physiological Argumentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Postoperative nausea and vomiting continue to be common in spite of advances in the techniques used in general anaesthesia. This is especially true in female patients (19,20). The frequency of postoperative emetic sequelae varies widely between different studies; figures as high as 83% have been reported (21).…”
Section: Many Pharmacological and Physiological Argumentsmentioning
confidence: 98%
“…It is well known that fentanyl anaesthesia is associated with a high frequency of postoperative nausea (20,21). The differences between different inhalation anaesthetics are controversial (4,25).…”
Section: Many Pharmacological and Physiological Argumentsmentioning
confidence: 99%